Analisis Strategi Peningkatan Produksi Budidaya Ikan Lele di Wilayah Batanghari (Jurnal Kendali Akuntansi, 2024)
This research was carried out in December 2023 at Batanghari. The location of this research is determined deliberately (purposive sampling) with the consideration that Batanghari has good potential to carry out catfish farming business activities. Business Catfish rearing cultivation in Batanghari has been established since 2010. The total income obtained by farmers in carrying out a catfish rearing business, namely Rp. 110.000.000 and the income is obtained for one harvest, and the annual income is Rp. 440.000.000. Based on results of calculating the percentage of profits obtained from cultivators Catfish in Batanghari is 500kg, 10 fish per kg. Meanwhile, the value of the cost of production is 3,944. The profit value for the selling price of catfish is IDR 8,006/kg.